Uji Performa Mesin Penggiling Padi dengan Rice Rubber Roller Horizontal: Performance Test of a Rice Milling Machine with a Horizontal Rice Rubber Roller - Suwandi, Dedi; Badruzzaman, Badruzzaman; Amat, Mohammad Azwar; Luthfi, Muhammad (Politeknik Negeri Indramayu, 2024)
Huller is the main machine that determines the quality and quantity of production in the rice milling industry. The current problem, especially in the small-scale rice milling industry, is that they still use locally made huller machines that use 6-inch diameter rice rubber rollers with a capacity of 800-1,200 kg/hour. Local huller machines produce a yield (broken rice) of 30-40%, so three huller machines and one polisher machine are needed in one production line. This machine assembly requires energy, human power and high costs. With these problems, a machine is needed that is capable of increasing the yield and milling capacity. Huller machine with horizontal rice rubber roller has a dimension specification of 1.3X0.9X2 meters; Rice rubber roller diameter 10 inches; 3 phase electric motor 20HP 15KW 1,500 rpm. The huller machine has been tested at the CV. Putra Maju rice mill, Wirakanan Village, Kandanghaur District, Indramayu Regency for 4 months. Test results Huller machine capacity 1,600 kg/hour ± 50 kg with a yield of 72% ± 2%.